2016
DOI: 10.1111/1471-0528.14056
|View full text |Cite
|
Sign up to set email alerts
|

Why women with previous caesarean and eligible for a trial of labour have an elective repeat caesarean delivery? A national study in France

Abstract: Objective To identify the characteristics of women and maternity units associated with elective repeat caesarean delivery (ERCD) in women eligible for trial of labour after caesarean (TOLAC).Design Cross-sectional study.Setting France.Population and sample Using data from the 2010 French National Perinatal Survey, a representative sample of births in France (n = 14 681 women), we studied two groups of women with prior caesarean section: (i) women eligible for TOLAC according to guidelines (n = 1179) and (ii) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
(73 reference statements)
3
16
3
1
Order By: Relevance
“…As expected, a previous vaginal delivery had a strong protective effect against ERCD, a finding that is in agreement with previous reports . In the present study, a previous vaginal delivery was strongly correlated with a preference for a vaginal delivery at the beginning of the index pregnancy (data not shown); however, regardless of this preference, a previous vaginal delivery had an independent protective effect on ERCD.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…As expected, a previous vaginal delivery had a strong protective effect against ERCD, a finding that is in agreement with previous reports . In the present study, a previous vaginal delivery was strongly correlated with a preference for a vaginal delivery at the beginning of the index pregnancy (data not shown); however, regardless of this preference, a previous vaginal delivery had an independent protective effect on ERCD.…”
Section: Discussionsupporting
confidence: 94%
“…However, both overall CD and ERCD rates are still higher than those reported for all women with a previous CD in Finland (47%) and Norway (54%) . A similar study in France showed an ERCD rate of 41.6% across the entire population and 28.4% among women without any characteristic that might indicate a repeat CD . Given the Brazilian recommendations for VBAC do not differ much from those in high‐income countries, it is likely that nonclinical factors, such as hospital policy, liability concerns, or provider preference, had a role in the decision to perform an ERCD, even within the public sector.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations